Donor Smoking Negatively Affects Donor and Recipient Renal Function following Living Donor Nephrectomy. (19th July 2011) - Heldt, Jonathan; Torrey, Robert; Han, Daniel; Baron, Pedro; Tenggardjaja, Christopher; McLarty, Justin; Lindler, Tekisha; Baldwin, D. Duane
Abstract : Background. While tobacco use by a renal transplant recipient has been shown to negatively affect graft and patient survival, the effect of smoking on the part of the kidney donor remains unknown. Methods. 29 smoking donors (SD) and their recipients (SD-R) as well as 71 non-smoking donors (ND) and their recipients (ND-R) were retrospectively reviewed. Preoperative demographics and perioperative variables including serum creatinine (Cr) and glomerular filtration rate (GFR) were calculated and stratified by amount of tobacco exposure in pack-years. Clinical outcomes were analyzed with a Student's t -test, chi-square, and multiple linear regression analysis (α = 0.05 ). Results. At most recent followup, SD-R's had a significantly smaller percent decrease in postoperative Cr than ND-R's (−57% versus −81%;P = 0.015 ) and lower calculated GFR's (37.0 versus 53.0 mL/min per 1.73 m 2 ;P < 0.001) . SD's had a larger percent increase in Cr than ND's at most recent followup (57% versus 40%;P < 0.001 ), with active smokers having a larger increase than those who quit, although this difference was not statistically significant (68% versus 52%;P = 0.055 ). Conclusions. Use of tobacco by kidney donors is associated with decreased posttransplant renal function, although smoking cessation can improve outcomes. Kidneys from donors who smoke should be used with caution.